Evaluation of trade and production policy in Iranian SME (a system dynamics model) - Farzad Haghighi-Rad; Ramin Ghadimi; Farshad Goldoust (Journal of Industrial Engineering International, 2019)
It is undeniable that SMEs face many management-related problems. These problems are often deeply rooted in the strategic decision making by managers. One of these decisions is associated with the production section. Many of these companies provide production infrastructure at high costs; however, they are unsuccessful in acquiring their market share. In these circumstances, providing a solution to the decision-making problem of managers in these companies can prevent the loss of capital. In this research, the system dynamics approach is used to test the hypothesis of a company's participation in the production field after securing a success in business activities of the market. In the present study, the SME performance model, proposed by Schmid's, is considered as the base model. After analyzing its construction steps according to managers' viewpoints, the model has been developed based on the conditions in Iran. Then, the research scenario is presented as follows. If an entrepreneur, before entering the production sector, tries to establish a customer network by conducting business activities, the organization's chance for success will increase. By defining a variable called 'production switch' and adding it as a function of a loyal customer network, the model has been tested. After simulating the model for a 5-year period, it is concluded that the rate of return on investment of an organization that has conducted the commercial activities at the outset of production is four times higher than that at the outset of production without the commercial activity.
Keywords: 650; System dynamics; Simulation; SMEs; Strategic management